(untitled) (KULT_online, 2024)
Negativity characterizes the contemporary. Today, elections, referenda, and political practice prefer not to; they reject and resist what is offered instead. The planetary polycrisis, on the other hand, limits what politics can do and reduces it to a condition of being limited. Therefore, The Big No and Negative Geographies engage in a theoretical conceptualization of negativity and explore negative phenomena from the perspective of political theory and cultural geography, respectively.